IMPROVEMENT OF RECIPE COMPOSITION AND TECHNOLOGICAL PROCESS OF PRODUCING VEGETABLE DISHES - Ahaian, Тamara; Bondarenko, Mariia; Savchenko, Alina; Honcharenko, Iryna (Biota. Human. Technology, 2023)
The article examines the peculiarities of the nutritional systems of different population groups, and gives a description of the chemical composition of fruits, vegetables, and mushrooms. The technological characteristics of vegetables, fruits and mushrooms are substantiated. Traditional methods of preparing vegetables and dishes made from them were examined, and a brief description of these methods was provided. To improve the cooking technology of vegetable dishes, the use of one of the innovative cooking methods, Sous-Vide, was proposed. The peculiarities of cooking food using the Sous-Vide method and its advantages compared to traditional cooking methods were indicated. The technology of preparing traditional vegetable stew, «Vegetable Stew» in an innovative way is presented, the calculation of technological parameters of improved dishes is given, and the organoleptic evaluation of the improved dish is analysed. The purpose of the article is to study the improvement of the recipe composition and the technological process of the production of dishes from baked vegetables, fruits and mushrooms. Methodology. Microbiological, physicochemical and organoleptic research methods. The scientific novelty is that new technologies for the production of dishes from baked vegetables, fruits and mushrooms have been developed, the recipe composition and technological process for the production of dishes from baked vegetables, fruits and mushrooms have been researched. Conclusions: dishes made from vegetables, fruits and mushrooms were developed, the technological process and recipes of well-known dishes were improved. It has been established that substituting mushrooms for potatoes contribute to a decrease in the product's energy value, allowing it to be enriched with vitamins and minerals necessary for the proper growth and development of the human body. By enriching dishes with vegetable proteins, it is possible to improve the diet of people and prevent the development of diseases associated with the lack of certain essential substances in the human body.